KEEFEKTIFAN PEMBELAJARAN CIRC DAN MODEL SINEKTIK PADA KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 12 KOTA MAGELANG - Suratiah, Siti; Suroso, Suroso (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2018)
(Title: The Effectiveness of CIRC Learning and Sinectic Models on Description Text Writing Skills Class VII Students of SMPN 12 Magelang). The purpose of this study was to identify comparison of the effectiveness between: (1) the use of CIRC; (2) the use of synectics; and (3) the use of CIRC and synectics methods in the teaching of descriptive text writing skill to junior secondary school students. The experimental design that is used is the pretest-post test control group design with two experimental groups, where treatments of CIRC and synectics methods were applied to each group, and one control group got the conventional learning method. The sample of this study was all of grade 7 students of Junior Secondary School 12 of Magelang Municipality.. The data were collected through assessment rubrics of descriptive text writing skills. The instrument was validated through the content validity with expert judgement. The data were analysed by Anova followed by Scheffe test. The research findings showed that: (1) CIRC method was more effective than conventional teaching method; (2) the synectics method was more effective than conventional learning method; and (3) the CIRC method was more effective than synectics method.Keywords: effectiveness, learning, circ, synectics, descriptive text writing.